PELATIHAN ECO-ENZYME - Brantasari, Mahkamah; Rohman, Abdul (Jurnal Pengabdian Kreativitas Pendidikan Mahakam (JPKPM), 2023)
Natural or organic food, the waste produced can of course be recycled as a form of further benefit. This organic waste has many benefits as long as it is managed properly. Eco enzymes are solutions of complex organic substances produced from the fermentation process of organic residues, sugar and water. This Eco-enzyme liquid is dark brown in color and has a strong sour or fresh aroma. This time, community service is carried out through training. Regarding Eco-Enzyme, it is felt that it is very necessary because of the benefits of Eco-Enzyme itself, apart from that, the other most important thing is regarding the ingredients used which are easy to obtain, for example, fruit peels and vegetable waste that are still good and fresh. , brown sugar and also clean water. Participants listened to presentations from resource persons regarding the benefits and also how to make Eco-Enzyme as well as the materials needed followed by the practice of making it.